2016
DOI: 10.1021/acs.jpcc.6b05216
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of PDTS-DTffBT-Based Solar Cell Performance through Control of Polymer Molecular Weight

Abstract: Herein, we investigated the effect of molecular weight (MW) on the efficiency of PDTS-DTffBT based polymer solar cells (PSCs). PDTS-DTffBTs with three different MWs were synthesized by controlling the polymerization conditions. The performance of PSCs improved significantly as the number-average molecular weight (M n) increased from 9 to 36 kDa. Combined with UV–vis absorption and electrochemical cyclic voltammetry measurements, the absorption properties and frontier orbital energy levels of the polymers were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Therefore, the M n could be easily affected by synthetic condition such as polymerization time, temperature, concentration, and so on . In recent years, a lot of reported works have demonstrated that the M n usually has great impact on the performance of PSCs via significantly affecting the molecular orientation, hole mobility, domain purity, and vertical composition profiles . However, a systemic study that clarifies the dependence of optimal thickness of active layer on polymer M n , which is of vital importance to develop a facile approach to realize high‐performance thick‐film PSCs, has not been made.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the M n could be easily affected by synthetic condition such as polymerization time, temperature, concentration, and so on . In recent years, a lot of reported works have demonstrated that the M n usually has great impact on the performance of PSCs via significantly affecting the molecular orientation, hole mobility, domain purity, and vertical composition profiles . However, a systemic study that clarifies the dependence of optimal thickness of active layer on polymer M n , which is of vital importance to develop a facile approach to realize high‐performance thick‐film PSCs, has not been made.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, to demonstrate the universal applicability of the air annealing method, we also used PDTS-DTffBT, which we reported before, 35,36 as polymer donor to fabricated PSCs and test the effect. The chemical structure of the materials and the J-V curves are showed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Such differences between E3a and Stille‐B1 in both OFETs and OPVs might be due to the end‐group effect present in polymers synthesized via Stille coupling (Fig. ), while other factors such as the polymer molecular weight and structural ordering might also play a role. The similar superior photovoltaic performance of phenanthridinone‐based conjugated polymers synthesized via DAP versus the same type of polymers synthesized via Suzuki coupling was also recently reported by Leclerc's group .…”
Section: Resultsmentioning
confidence: 99%